Precalculus

posted by .

I keep getting wrong answer for this question.

Write as a single logarithm

log(x+1)+2log(2x+1)-log(x-3)

  • Precalculus -

    See previous post.

  • Precalculus -

    I got 4x^3+8x^2+5x+1/(x-3)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    write as a single logarithm: -2logbase3(1/x)+(1/3)logbase3(square root of x) please show the steps to solving this. thanx. remember that 1 log (AxB) = log A + Log B (same base) 2 log (A/B) = log A - log B 3 log A^n = n log A use these …
  2. math

    Logarithm!!! Select all of the following that are true statements: (a) log(2x) = log(2) + log(x) (b) log(3x) = 3 log(x) (c) log(12y) = 2 log(2) + log(3y) (d) log(5y) = log(20y) – log(4) (e) log(x) = log(5x) – log(5) (f) ln(25) …
  3. Precalculus

    Write the given expression as a single logarithm. log(70x)+log(10y)-2
  4. Algebra

    How would I write 1-2log(7)x as a single logarithm Choices: log(7) x^2/7 log(7) 7x^2 log(7) 7/x^2 log (7) x^2 Thank you
  5. Precalculus

    What am I doing wrong? I keep getting 48 and its wrong... Solve 2log(x)-log(4)=3log(4) 2log(x)-log(4) log(x/4)=3log4 log(x/4)=log12 x=48
  6. Precalculus-Verify

    log(base2)x-log(base2)6= log(base2)5+ 2log(base2)3 log(x/6)=3log15 (x/6)=15^3 6*(x/6)=15^3*6 x=15^3*6 =20,250 Answer is 270.... What did I do wrong...
  7. Precalculus

    Write as a single logarithm log(x+1)+2log(2x+1)-log(x-3)
  8. Precalculus

    I keep getting wrong answer for this question. Write as a single logarithm log(x+1)+2log(2x+1)-log(x-3)
  9. Math

    solve log(7x-3)+2log(5)=2+log(x+3) I've attempted to do this question and I ended up with log(7-3)+log(5^2)-log(x+3)=2 but I don't what to do next or whether I did something wrong.
  10. Advanced Functions/ Precalculus Log

    1. Evaluate 4^(log base4 64) + 10^(log100) 2. Write 1+log(base2)x^3 as a single logarithm 3. Write log(base b)√(x^3 y z^6) 4. Solve log(base 2)x-log(base 2)6=log(base 2)5+2log(base 2)3 5. Solve 3^(2x) = 9(81^x) 6. Solve 3^(2x)=7^(3x-1). …

More Similar Questions